2018
DOI: 10.1002/asi.23988
|View full text |Cite
|
Sign up to set email alerts
|

Art in an algorithm: A taxonomy for describing video game visual styles

Abstract: The discovery and retrieval of video games in library and information systems is, by and large, dependent on a limited set of descriptive metadata. Noticeably missing from this metadata are classifications of visual styledespite the overwhelmingly visual nature of most video games and the interest in visual style among video game users. One explanation for this paucity is the difficulty in eliciting consistent judgements about visual style, likely due to subjective interpretations of terminology and a lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The result of this study shows that the participants, as expert users who create video game art, tend to assign more terms about techniques that are used to create particular visual styles. Unlike the prior user testing of the existing visual style taxonomy by Cho et al [3], where the authors found that general game users did not typically use technique-related terms when they were asked to describe the visual style of sample game screenshots [3], our participants did self-generate and offer several technique-related terms. This is especially true for the six artists (as opposed to the two programmers) who tended to provide more descriptors on different techniques.…”
Section: Purposes and Structure Of Metadata Schemamentioning
confidence: 87%
See 2 more Smart Citations
“…The result of this study shows that the participants, as expert users who create video game art, tend to assign more terms about techniques that are used to create particular visual styles. Unlike the prior user testing of the existing visual style taxonomy by Cho et al [3], where the authors found that general game users did not typically use technique-related terms when they were asked to describe the visual style of sample game screenshots [3], our participants did self-generate and offer several technique-related terms. This is especially true for the six artists (as opposed to the two programmers) who tended to provide more descriptors on different techniques.…”
Section: Purposes and Structure Of Metadata Schemamentioning
confidence: 87%
“…The Video Game Metadata Schema (VGMS) was established as a result of this project. The schema was created based on multiple approaches involving domain analysis and a series of user studies, and was tested and modified several times [3] [10] [14]. The existing visual style taxonomy was also created and tested in a prior user study [3], but primarily with general game players.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare photorealistic visuals in Mela , photographs were taken (by the game development team or the first author), converted into cartoon format and edited as needed using software (see Figure 10). In few places in Mela , the black and white style (Figure 11) also has been used, which is defined as “a style that mainly portrays characters or environments in shades of black and white” (Cho et al, 2018, p. 637).
Figure 10.Converting real photos into cartoon using software.
Figure 11.Black and white visual style was used in few places of Mela game.
…”
Section: Applied Methods In the Design Of Melamentioning
confidence: 99%
“…Visual Elements in Mela. To make the visuals as realistic as possible for the player, images in the Mela game are mainly based on what Cho et al (2018) referred to as photorealism style. To prepare photorealistic visuals in Mela, photographs were taken (by the game development team or the first author), converted into cartoon format and edited as needed using software (see Figure 10).…”
Section: Aesthetics In Melamentioning
confidence: 99%